Analysis of Character Education Value in the Zootopia Movie - Miranda Tarigan; Yunike Br Ginting; Merry Susanti Tarigan; Elita Modesta Br Sembiring (Jurnal Ilmiah Wahana Pendidikan, 2022)
Zootopia Movie. The reason the researchers chose this movie is because this movie really displays good character education so that this movie can be reached by all people. From the result obtained, the value of character education contained in the Zootopia Movie is fourteen. The researchers concludes that this movie really shows the character about struggle, hard work, and responsibility in everything as a police officer